Management trends and outcomes of pineal germinoma in a multi-institutional Australian cohort. (August 2021) - Stephens, Sean; Kuchel, Anna; Cheuk, Robyn; Alexander, Hamish; Robertson, Thomas; Rajah, Thulasi; Tran, Quan; Inglis, Po-ling
Highlights: Outcomes following chemo-radiotherapy for pineal germinoma are excellent. Multidisciplinary care optimises the diagnosis and treatment of pineal germinoma. The utility of biomarkers and immunotherapy in germinoma remains uncertain. Abstract: Pineal germinoma is rare with high cure rates following craniospinal radiotherapy. Efforts to reduce the radiotherapy dose and field via combination with chemotherapy suggest comparable disease control and reduced neurocognitive impairments, while the efficacy of immunotherapy in pineal germinoma remains undetermined. This report aimed to review clinical outcomes in patients treated for pineal germinoma in Queensland, Australia, and assess for Programmed Death-Ligand1 (PD-L1) expression. Patients who commenced radiation and/or chemotherapy for pineal germinoma from 2005 to 2017 were retrospectively identified using Queensland Oncology Online database. Demographic, diagnostic, treatment, and outcome data was obtained from electronic medical records. PD-L1 immuno-histochemistry was performed on available specimens. Eighteen patients with long-term follow-up data were identified. Median age at diagnosis was 16.8 years (range 9–46 years). Diagnosis was made histologically in fifteen patients, and radiologically in three. All patients underwent radiotherapy (median 36 Gy (range 21–54 Gy)) with lower median dose delivered with whole ventricle irradiation (12/18patients) than craniospinal irradiation (5/18patients). Sixteen patients received chemotherapy preceding radiotherapy. All patients are alive at median 7.25 years from primary treatment completion (range 2.03–13.1 years). Relapse occurred in three patients (16.67%) following treatment response, all of whom achieved remission following high-dose chemotherapy with stem-cell support and craniospinal radiotherapy. Post-treatment functional outcomes were similarly excellent. PD-L1 expression was low (1–49% cells) or negative in 87% of tumours tested but results were confounded by specimen quality and availability. Reduced-dose radiotherapy with chemotherapy does not compromise outcome and is standard of care at this institution. Immunotherapy is unlikely to become standard treatment in the near future.